2022
DOI: 10.1002/slct.202203166
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Water‐Soluble Polythiophene/Poly (sulfonic acid diphenyl aniline)/Polyethylene Oxide Electrospun Nanofibers and Their Antioxidant Activities

Abstract: The fabrication and antioxidant properties of polythiophene/ poly(sulfonic acid diphenyl aniline)/polyethylene oxide electrospun nanofibers obtained in this study were brought to the literature for the first time. For this, polythiophene/poly(sulfonic acid diphenyl aniline)/polyethylene oxide (PTh/PSDA/PEO) nanofibers containing 5, 10, 20 and 40 % PTH/PSDA composite by weight were produced by electrospinning method. According to both CUPRAC and ABTS assays, these electrospun nanofibers were found to have antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We previously reported that PTh/PSDA/PEO electrospun nanofibers showed antioxidant activity by both ABTS and CUPRAC assays. [ 14 ] It was observed that the PTh/PSDA/PEO nanofiber with the highest PTh/PSDA ratio had the highest antioxidant activity with 111 and 244 μg TE/mg according to both ABTS and CUPRAC assays. In this study, the highest antioxidant value obtained according to the CUPRAC assay, 614 μg TE/mg is more than 2.5 times the 244 μg TE/mg.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that PTh/PSDA/PEO electrospun nanofibers showed antioxidant activity by both ABTS and CUPRAC assays. [ 14 ] It was observed that the PTh/PSDA/PEO nanofiber with the highest PTh/PSDA ratio had the highest antioxidant activity with 111 and 244 μg TE/mg according to both ABTS and CUPRAC assays. In this study, the highest antioxidant value obtained according to the CUPRAC assay, 614 μg TE/mg is more than 2.5 times the 244 μg TE/mg.…”
Section: Resultsmentioning
confidence: 99%
“…Here, Polythiophene/poly(sulfonic acid diphenyl aniline)/polyethylene oxide (PTh/PSDA/PEO) electrospun nanofibers showed antioxidant activity according to both 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS) and CUPRAC tests. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation